(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
This article examines the historical and philosophical stages of social consciousness transformation in Uzbekistan from the Jadid reform movement of the late nineteenth and early twentieth centuries to the contemporary New Uzbekistan development strategy. The study investigates the evolution of social consciousness through the lenses of enlightenment, national identity, modernization, independence, and democratic renewal. Employing historical-philosophical, comparative, hermeneutic, and systemic research methods, the article identifies the principal factors that shaped changes in collective consciousness across different historical periods. The findings demonstrate that Jadidism laid the intellectual foundation for modern national consciousness, while the independence era and the New Uzbekistan reforms introduced new paradigms of civic responsibility, social participation, and humancentered development. The research proposes a conceptual model of social consciousness transformation based on continuity, modernization, and value-based renewal. The article contributes to contemporary discussions regarding social development, national identity, and philosophical modernization in Uzbekistan